ANTI-PSORIATIC EFFECT OF WRIGHTIA TINCTORIA (SHWETA KUTAJA): A REVIEW STUDY - Singhal Priyanka; Sharma Shivam (International Journal of Applied Ayurved Research, 2018)
Psoriasis is a chronic inflammatory, hyper proliferative skin disease, characterized by well-defined erythematous skin plaques, particularly affecting extensor surfaces and scalp and usually follows a relapsing and remitting course. Psoriasis can be corrected with kitibha kushtha in Ayurveda. It has become a global problem inspite of advances in modern science. Ancient science of Ayurveda has discussed psoriasis in length thousands of years ago. The incidence of psoriasis among total skin patients ranged between 0.44 and 2.2%, with overall incidence of 1.02%.Number of psoriasis patients are increasing in very high range. Year by year, its growing spread is very fast. In Ayurveda, there are many ways to prevent psoriasis and to cure its complications. Wrightia tinctoria extracts possess superior antipsoriatic activity than betamethasone and retiny acetate (vitamin A topical formulation). In this paper, we are trying to explain the anti-psoriatic effect of shweta kutaja (Wrightia tinctoria).